An economic and environmental assessment of biofuel produced via microwave-assisted catalytic pyrolysis of forest residues. (1st July 2022) - Zhu, Hui; Saddler, Jack; Bi, Xiaotao
Graphical abstract: Microwave-assisted catalytic pyrolysis (MACP) is a low-carbon emission and economically feasible technology for co-producing biofuels and biochar from biomass. Highlights: MACP coupled with low-carbon electricity mix is a promising negative emission technology. The use of electricity for MACP biofuel production generates significant GHG reduction without sacrificing the travel distance of vehicles compared to directly charged EVs. The application of biochar has significant impacts on economic and environmental performances of MACP system. MACP biofuel will be competitive in price compared to petroleum fuels by 2026 under the planned carbon tax schedule in Canada. The co-production of biofuel and biochar brings flexibility to the biorefinery to seek the highest possible economic and environmental benefits. Abstract: The conversion of forest residues into biofuels will enhance the decarbonization of the transportation sector and help the world reach its net-zero targets. Microwave-assisted catalytic pyrolysis (MACP) is an emerging thermo-catalytic conversion technology which, when coupled with low-carbon electricity, will result in negative emissions. The work described here assessed the economic feasibility and environmental impact of a novel MACP system for co-production of upgraded biofuel and high-quality biochar from forest residues. The cradle-to-gate (CTG) carbon intensity of MACP biofuel ranged from −57.3 to 27.4 g CO2 -eq/MJ respectively when using either low-carbon electricity or carbon-intense electricity. Compared to petroleum fuels, a 43% to 162% reduction of GHG emissions could be achieved depending on electricity mix and methods to treat biochar co-product. The use of electricity to produce MACP biofuel as compared to directly charge electric vehicles was justified as a preferred use based on the finding that the advanced utilization of waste biomass via MACP could contribute significantly to GHG reduction of transportation fuel without sacrificing the travel distance of vehicles. The minimum selling price (MSP) of MACP biofuel was 1.02/L in the absence of any policy support and could be reduced to a comparable price of petroleum fuels at 0.53/L or increased to 1.32/L depending on the co-product revenue from biochar's higher or lower-value applications. MACP biofuel could also be priced competitively with petroleum fuels by as early as 2026 under the planned carbon tax schedule in Canada. This co-production of upgraded biofuel and value-added biochar could bring flexibility to the biorefinery to seek the highest possible economic and environmental benefits facing the changing market and policy.